Periodic codings of Bratteli-Vershik systems - Frick, Sarah; Petersen, Karl; Shields, Sandi (MATHEMATICA SCANDINAVICA, 2020)
We develop conditions for the coding of a Bratteli-Vershik system according to initial path segments to be periodic, equivalently for a constructive symbolic recursive scheme corresponding to a cutting and stacking process to produce a periodic sequence. This is a step toward understanding when a Bratteli-Vershik system can be essentially faithfully represented by means of a natural coding as a subshift on a finite alphabet.